Spatial-temporal analysis of built-up land development in landslide-prone areas: Disaster risk assessment - Rakuasa, Heinrich (Calamity: A Journal of Disaster Technology and Engineering, 2025)
Background: This study aims to analyze the development of built-up land in landslide-prone areas in Ambon City from 2014 to 2024, considering the increased disaster risk due to unplanned urbanization. Methods: The methods used include spatial temporal analysis utilizing Landsat 7 and Landsat 8 satellite imagery data, as well as landslide risk maps from the National Disaster Management Agency (BNPB). Findings: The results showed that built-up land in high-risk areas increased sharply, from 429.91 hectares in 2014 to 951.65 hectares in 2024, potentially increasing vulnerability to landslides. Conclusion: The study recommends the need for stricter spatial policies and better risk management to control development in landslide-prone areas. In conclusion, wise management and integration of landslide risk maps in urban planning are essential to mitigate the negative impacts of land use change and protect communities from disasters. Novelty/Originality of this article: This study offers a unique contribution by combining spatial-temporal analysis using Landsat satellite imagery with landslide risk maps to assess the impact of unplanned urbanization on landslide-prone areas, providing new insights into the relationship between urban development and disaster risk in Ambon City.